2014
DOI: 10.1111/weng.12080
|View full text |Cite
|
Sign up to set email alerts
|

The progressive aspect in the Netherlands and the ESL/EFL continuum

Abstract: This paper responds to calls to (i) approach varieties of English as a native (ENL), second (ESL) and foreign (EFL) language in an integrated fashion, and (ii) widen the scope of world Englishes analyses to the Expanding Circle. It describes the development of the Corpus of 'Dutch English', the first Expanding Circle corpus incorporating all text types in the written components of the ICE corpora. This corpus has implications for the description of English in the Netherlands in particular and for the investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 58 publications
4
21
0
Order By: Relevance
“…Hence, with regard to the usage of the progressive form, learner Englishes do not emerge as categorically different from second language varieties. Overall, the results of this study support the notion of a continuum between learner English and second language varieties (Gilquin & Granger ; Edwards , ). The finding that Finnish and Swedish learners have adopted the new non‐aspectual functions of the progressive due to extensive informal exposure to English is illustrative of the development that second language‐like environments are emerging in countries of the Expanding Circle (Edwards ; Laitinen & Levin ).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Hence, with regard to the usage of the progressive form, learner Englishes do not emerge as categorically different from second language varieties. Overall, the results of this study support the notion of a continuum between learner English and second language varieties (Gilquin & Granger ; Edwards , ). The finding that Finnish and Swedish learners have adopted the new non‐aspectual functions of the progressive due to extensive informal exposure to English is illustrative of the development that second language‐like environments are emerging in countries of the Expanding Circle (Edwards ; Laitinen & Levin ).…”
Section: Resultssupporting
confidence: 86%
“…Studies by Edwards (, ) and Laitinen and Levin () show that it is too early to conclude that foreign language learners/users do not extend the progressive to new contexts (Hundt & Vogel ). Most of the earlier studies that have found foreign language learners to stick to prototypical uses of the progressive have been limited to written data by learners with non‐aspect L1s (German, Swedish, Finnish) and with relatively advanced levels of English proficiency.…”
Section: The Progressive Form As An Object Of Studymentioning
confidence: 99%
“…EFL has features in terms of lexis, grammar and pronunciation that are different from English as spoken in Inner Circle countries, that is, "the traditional cultural and linguistic bases of English" (Kachru, 1992, p. 356), such as Australia, the UK and the USA. For instance, Edwards (2014) shows that Dutch non-native speakers of English use the progressive aspect for stative verbs where Inner Circle speakers would use simple tenses. Such deviations from Inner Circle norms are traditionally regarded as second language (L2) errors (Bartsch, 1987, as cited in Hamid & Baldauf, 2013; see also Edwards, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Edwards (2014) shows that Dutch non-native speakers of English use the progressive aspect for stative verbs where Inner Circle speakers would use simple tenses. Such deviations from Inner Circle norms are traditionally regarded as second language (L2) errors (Bartsch, 1987, as cited in Hamid & Baldauf, 2013; see also Edwards, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…2011, Edwards and Laporte 2015, Gilquin 2015, Gries and Deshors 2015. Therefore, studies such as Deshors (2014), Edwards (2014Edwards ( , 2016 and Gilquin and Granger (2011) have called into question the traditionally assumed divide between EFL and ESL by showing that it is not necessarily clear-cut. For instance, Deshors (2014: 298) concludes that "within the EFL-ESL continuum, individual world and learner variants are intermingled rather than grouped together according to 'type' and positioned distinctively closer or further away from the native variant".…”
Section: Introductionmentioning
confidence: 99%